Impacts of osteoporosis on quality of life in elderly women - Abolfazl Mohammadbeigi; Jafar Hassanzadeh; Narges Mohammadsalehi; Bagher Nasimi; Gholamhossein Ranjbar-Omrani (Chronic Diseases Journal, 2013)
BACKGROUND: Osteoporosis, the most common pathological cause of skeletal weakening and the most common metabolic bone disease, is caused by loss of bone mass density (BMD). Fractures due to osteoporosis will worsen life, increase pain, and decrease quality of life. The present study aimed to determine the impact of osteoporosis on quality of life among elderly women.